Mary Radcliffe
due 2 May 2014
In Bartle:
5C. If f L(X, F, ) and g is a Fmeasurable realvalued function
such
R
R that
f (x) = g(x) almost everywhere, then g L(X, F, ) and f d = g d.
+
Proof. Let h(x) = f (x) g(x). Then h M
R (X, F), and h = 0 almost
everywhere. Therefore, h is integrable and h d = 0. But
R this implies
(f g) d
that
f
g
is
integrable,
and
thus
g
is
integrable.
Moreover,
R
R
h d = 0, and thus (f g) d = 0. The result immediately follows by
linearity of integration.
Notice, if a, b R, then a2 + b2 =
(a + b)2 2ab
(a + b)2 =
a + b a + b. Therefore, if f is integrable, then f  is a measurable
function such that f  f1  + f2 , and thus by Corollary 5.4, f  is
integrable.
Conversely, if f  is integrable, note that f1  < f  and f2  < f , so we
have f1 and f2 are realvalued integrable functions by Corollary 5.4. But
then by definition f is also integrable.
R
R
For the inequality, write f d = rei , so thatR f d R= r. Let g(x) =
ei fR(x), so that g(x) = g1 (x)R + ig2 (x), and g d = ei f (x) d =
ei f (x) d = r. But then g2 d = 0, so g2 = 0 almost everywhere.
Moreover, f  = ei f  = g = g1  almost everywhere.
Therefore, we have
Z
Z
Z
Z
Z
f d = r = g1 d = g1 d g1  d = f  d,
1
f

d
lim
fn
n
R
R
f  d = 0, and thus lim fn  d = f  d
R
5Q. If t > 0, then 0 etx dx = 1t . Moreover, if t a > 0, then etx eax .
Use this and Exercise 4M to
justify differentiating under the integral sign
R
and to obtain the formula 0 xn ex dx = n!.
Proof. Now,
Z
etx dx
Z
=
lim
etx dx
b
1 tx
lim e
b
t
x=0
1 tb 1
lim e
+
b
t
t
1
,
t
=
=
=
xetx d(x).
large, we have that xn < ex/4 , so as above, we have that xn e 2 is integrable on [0, ). Then as above, we have
Z
d (n 1)!
d
n!
n1 tx
=
x
e
dx
n+1 =
t
dt
tn
dt
0
Z
n1 tx
=
(x
e )d(x)
[0,) t
Z
xn etx dx.
=
0
as desired.
5T. Let f be a Fmeasurable function on X to R. For n Z+ , let {fn }
be theR sequence of Rtruncates of f . If f is integrable
with respect to ,
R
then f d = lim fn d. Conversely, if sup fn  d < , then f is
integrable.
Proof. Note that for all
R n, we have
R fn  f , and thus if f is integrable,
the DCT implies that fn d f d.
For the converse, note that fn  is a monotonically increasing sequence
of
R nonnegative
R functions with limit f , and Rthus the MCT implies that
fn  d f  d. Thus, by hypothesis, f  d < , and therefore
f  and thus f are integrable.
4O. Fatous Lemma has an extension to a case where
R the fn take on negative
values. Let h M + (X, F), and supposeR that h d < . If {f
R n } is a
sequence in M (X, F) and h fn then lim inf fn d lim inf fn d.
3
= lim arctan(n) = .
n
2
For the other part, notice that 1+nn2 x2 n2nx2 nx1 2 x12 , and
R
moreover, 1 x12 = 1 < , so x12 L([1, ), L, ). Therefore, by
the dominated convergence theorem, we have
Z
Z
n
n
lim
dx
=
lim
d(x)
2
2
2 2
n 1
n
1+n x
[1,) 1 + n x
Z
n
d(x)
=
lim
2 2
[1,) n 1 + n x
Z
=
0d(x) = 0.
[1,)
1+n2 x2 dx = 2 .
x n
ex , and as cos( nx ) 1,
n)
n
Thus, 1 + nx
log(2+cos( nx ))
=
4
log(3)
Rt
2
2. Let f (t) = 0 ex dx. We will use DCT to evaluate limt f (t), even
without being able to evaluate the indefinite integral.
(a) Put h(t) = f (t)2 and g(t) =
g 0 (t).
(b) Show that h(t) + g(t) =
R1
0
et (1+x
1+x2
2)
for all t.
Z
.
2
ex dx =
Solution. (a) Note that h0 (t) = 2f (t)f 0 (t) = 2et f (t), by the fundamental theorem of calculus.
h t2 (1+x2 ) i
t2 (1+x2 )
e
For g 0 (t), let f (x, t) = e 1+x2 , and note that t
=
1+x2
2
2
at t = 12. Therefore, 2tet 2/e =: C for all t. Thus,
2 2
f
t Cet x C, which is clearly integrable on [0, 1]. Therefore,
by Theorem 5.9,
"Z
#
!
Z 1
2
2
1 t2 (1+x2 )
d
e
et (1+x )
dx
=
dx
dt 0
1 + x2
1 + x2
0 t
Z 1
2
2
=
2tet (1+x ) dx
0
=
=
2tet
2e
t2
0
t
et
x2
dx
eu du
as desired.
5
4,
/4 =
2 .
Extras:
5A. If f L(X, F, ) and a > 0, show that the set {x X  f (x) > a}
has finite measure. In addition, the set {x X  f (x) 6= 0} has finite
measure.
R
Proof. As f  L, we have that f  d = A < . Let Ea = {x
X  f (x) > a}. Then we have f  = f Ea + f Eac aEa + f Eac ,
and thus
Z
Z
A = f  d a(Ea ) +
f  d a(Ea ).
Eac
L,
and
thus
f
L.
Moreover,
R
and thus f d = 0.
5D. If f L(X, F,
R ) and > 0, then there exists a measurable simple function
such that f  d < .
Proof. As f + and f are M + , we have measurable
simple functions
+
R
R
and such that + f + , f , and (f + + ) d < 2 , (f
) d < 2 . Let = + . Then we have is simple, and
Z
Z
Z
f  d = f + + (f ) d
f + +  + (f ) d < .
5G. Suppose
that f L(X, F, ), and that its indefinite integral is (E) =
R
f
d
for
E F. Show that (E) 0 for all E F if and only if
E
f (x) 0 for almost all x X. Moreover, (E) = 0 for all E if and only
if f (x) = 0 for almost all x X.
Proof. Write f = f + f . Suppose (E) > 0 for all E F. Let
> 0, and Rput E = {x X  f (x) < }. As f is measurable, E F.
Moreover, E f d (E ) 0, and thus (E ) = 0. But then {x
X  f (x) < 0} = nZ+ E1/n has measure 0, and therefore f 0 almost
everywhere.
On the other hand, if f 0 almost everywhere,R then for all E F,
f E 0 almost everywhere, and thus by 5B, f E d 0 for all
E F.
For the second piece, we repeat the above argument with E = {x
X  f (x) > }.
5H. Suppose that f1 , f2 L(X, F, ), and let 1 , 2 be their indefinite integrals. Show that 1 (E) = 2 (E) for all E F if and only if f1 (x) = f2 (x)
for almost all x X.
Proof. Note that 1 (E) = 2 (E) for all E if and only if (1 2 )(E) = 0
for all E, if and only if f1 f2 = 0 almost everywhere (by problem
G).
Much more than documents.
Discover everything Scribd has to offer, including books and audiobooks from major publishers.
Cancel anytime.